Hadith-Based Ethics: Neighborly Social Relations In The Prophetic Tradition - Budiman, Arif; Sukandar, Warlan; Safri, Edi; A'yun, Qurrota; Etika, Indah (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
This article investigates the model of neighborly social relations as a practical and behavioral manifestation in the tradition of the Prophet Muhammad S.A.W. The study employs an interdisciplinary approach to analyze the ethical corpus of hadith through thematic-correlative exploration, aiming to actualize the values of neighborliness in the contemporary context. The study examines traditions on neighborly ethics contextualized using the structural-functionalism theory. A qualitative method based on desk-based data was employed, while the content analysis identified configurations of positive social relationships in the canonical hadith collection. These relationships are oriented towards assertive-responsive and affective-responsive values that guide Muslims in balancing rights and obligations to create mutual harmony. Neighborly relations, as emphasized in the hadith as a reflection of faith, contribute significantly to creating solidarity and harmony in local and global communities. By integrating the perspectives of structural functionalisms of Talcott Parsons and Emile Durkheim, this study offers a systematic framework for understanding and applying the ethical values in the hadith. The article argues that such values are essential for individual moral development and for maintaining social cohesion. The results of this study highlight the relevance of hadith-based neighborly ethics as a universal mechanism for promoting peaceful coexistence in modern societies.